Reframing Educational Administration Innovation in Primary Schools: Evidence-Informed Governance for Effective Learning Environments - Meli Tiara (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2026)
This study reconstructs research on innovative educational administration in primary schools by replacing an under-specified single-case design with a structured integrative review and contextual evidence-mapping approach. The source manuscript positioned SDN 1 Banding Agung as an empirical case but did not report participant numbers, sampling logic, interview protocols, observation duration, or auditable primary-data extracts. To preserve analytical integrity, school-specific descriptions are therefore treated as contextual descriptors, while claims about mechanisms and outcomes are grounded in recent peer-reviewed evidence. Sixteen academic sources published between 2019 and 2025, supplemented by an authoritative international education report, were synthesized across five domains: strategic leadership, collaborative governance, teacher professional and digital capacity, equity-responsive resource management, and continuous evaluation. The synthesis indicates that administrative innovation influences learning environments primarily through indirect organizational mechanisms. Meta-analytic evidence links principal practices to teacher well-being, instructional practice, organizational health, and student outcomes, while longitudinal and review evidence highlights teacher collaboration, collective efficacy, digital competence, and coherent implementation routines as critical mediators. Digitalization contributes when it strengthens decision quality, communication, professional learning, and instructional responsiveness, but technology availability alone is insufficient. The study proposes an Integrated Administrative Innovation-to-Learning Environment Framework for resource-sensitive primary schools. Its contribution lies in shifting the unit of analysis from isolated innovations to the governance architecture that enables innovations to become sustainable learning conditions.